Unveiling Key Drivers of Consumer Purchase Decisions in the Evolving Cosmetics Industry - Kesuma Suryawan, Tjokorda Gde Agung Wijaya; Meiyani, Gusti Ayu Eva (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2024)
This study examines the influence of brand image, word-of-mouth (WOM), and competitive advantage on purchasing decisions in the cosmetics sector, focusing on CRRANTE products at Mutiara Permai Cantika Cosmetics Store, Gianyar, Bali, Indonesia. Utilizing a quantitative, causal-associative approach, data were collected from 96 respondents through purposive random sampling. The analysis included validity and reliability tests, classical assumption tests, multiple linear regression analysis, determination analysis, as well as F-test and t-tests to evaluate the simultaneous and partial effects of the independent variables on purchasing decisions. The findings reveal that brand image, WOM, and competitive advantage have a positive and statistically significant impact on purchasing decisions both individually and collectively. These results emphasize the importance of fostering a strong brand image, leveraging positive WOM, and maintaining a competitive edge to influence consumer behavior effectively. This research contributes to the field of international marketing by providing valuable insights into consumer decision-making processes within a highly competitive local cosmetics market. It offers practical implications for businesses aiming to strengthen their market position and academic value for further exploration of purchasing dynamics in similar contexts.